Reversal of Novel Anticoagulants in Emergent Surgery and Trauma: A Comprehensive Review and Proposed Management Algorithm - Palaiodimos, Leonidas; Miles, Jeremy; Kokkinidis, Damianos G.; Barkolias, Christos; Jonnalagadda, Anil K.; Papaconstantinou, Dimitrios; Frountzas, Maximos; Misiakos, Evangelos P.; Schizas, Dimitrios (Current Pharmaceutical Design, 2018)
Non-vitamin K oral anticoagulants (NOACs), including dabigatran, rivaroxaban, apixaban, and edoxaban, are increasingly used for thromboembolism prevention. Contrary to older anticoagulants, such as coumadin, when antidotes existed and were broadly used in cases of emergent surgery and bleeding, antidotes for NOACs have not been developed until recently. Moreover, the monitoring of NOAC's anticoagulant effect varies across different hospital settings and the absence of a single test that can accurately predict the degree of anticoagulation achieved increases the uncertainty. These uncertainties often result in management dilemmas for clinicians when patients who are on NOACs need a reversal of anticoagulation. Until recently, available antidotes for NOACs included only prothrombin complex concentrate (PCC), activated prothrombin complex concentrate (aPCC) and recombinant activated factor VII and the less optimal fresh frozen plasma (FFP). Recently though, novel antidotes for NOACs have been developed, including idarucizumab, which is a monoclonal antibody fragment that binds dabigatran, and andexanet alfa, a modified decoy form of the activated factor X (FXa) that binds FXa inhibitors and AT III. Another option, ciraparantag, which is a small molecule that binds to heparin, thrombin inhibitors and FXa inhibitors, is still in phase I development. In this review, we summarize the current evidence and present the available bypassing and novel reversal agents. Finally, we propose an algorithm for the management of patients who take NOACs and present to the emergency department with either trauma and active bleeding or need for emergent surgery.
Keywords: Anticoagulation